2011
DOI: 10.1111/j.1444-0938.2010.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal imaging with slit‐scanning and Scheimpflug imaging techniques

Abstract: Modern anterior segment imaging techniques, such as slit-scanning and Scheimpflug imaging, greatly improved the field of corneal imaging. Devices such as the Orbscan (Bausch & Lomb Surgical, Inc) and, more recently, the Pentacam (Oculus, Inc) and the Galilei (Ziemer Ophthalmic Systems AG) have brought a whole new range of clinical possibilities and sparked interest in the academic community. These new tomographers create three-dimensional models of the cornea and enable the direct measurement of both the anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 88 publications
(219 reference statements)
0
58
0
5
Order By: Relevance
“…Thus, cycloplegic refraction examinations provided more reliable results in all age groups (17,19) . Recent developments in imaging techniques allow the clinician to quantitatively calculate anterior segment parameters, such as keratometry, CCT, ACD, ACV, and ACA (5,20) . Among these new technologies, the Pentacam device is a rotating Scheimpflug system that allows for the noninvasive assessment of the anterior chamber structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, cycloplegic refraction examinations provided more reliable results in all age groups (17,19) . Recent developments in imaging techniques allow the clinician to quantitatively calculate anterior segment parameters, such as keratometry, CCT, ACD, ACV, and ACA (5,20) . Among these new technologies, the Pentacam device is a rotating Scheimpflug system that allows for the noninvasive assessment of the anterior chamber structures.…”
Section: Discussionmentioning
confidence: 99%
“…The device also analyzes the corneal central radii, corneal asphericity, various colored maps of curvature and elevation, corneal pachymetry, crystalline lens densitometry, and the complete anterior chamber (anterior chamber depth, volume, and angle). The measurements are all non-contact and are free of discomfort to the patient (1,5) .…”
Section: Devices Used In the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Both machines gave values comparable with the points lying along the line of equality, with small limits of agreements (Figures 1 and 2). Previous studies have reported good correlations between both machines in either pachymetry or corneal power measurements (6)(7)(8) . One of the main diagnostic tools for keratoconus and keratectasia is abnormal topography.…”
Section: Discussionmentioning
confidence: 81%
“…There are currently five devices on the market that are based on these technologies: Orbscan IIz (Bausch & Lomb Surgical, Inc), Pentacam (Oculus, Inc), the Galilei (Ziemer Ophthalmic Systems AG,) the Precisio (Ligi Tecnologie Medicali), and the Sirius (CSO Ophthalmic). The Orbscan IIz is the only slit-scanning-based technology; the others involve Scheimpflug-based technology [2].…”
Section: Introductionmentioning
confidence: 99%